Storage stability, color kinetics and morphology of spray-dried soursop (Annona muricata L.) powder: effect of anticaking agents - Chang, Lee Sin; Karim, Roselina; Sabo Mohammed, Abdulkarim; Yusof, Yus Aniza; Mohd Ghazali, Hasanah (Taylor & Francis Open, 2018)
Soursop is a tropical fruit that undergoes postharvest deterioration rapidly. Conversion into powder is an ave nue to value-add the fruit as it helps to reduce postharvest losses. Although powder production is not complicated, studies have shown that caking is a common problem often associated with fruit powders. Thus, an addition of a food additive is needed to improve the storage stability of powders. In this study, soursop powder was produced by spray-drying an enzyme-liquefied soursop puree incorporated with either tricalcium phosphate (TCP) or calcium silicate (CS), at three different concentrations (0.5, 1.0, and 1.5% w/w). The control was considered powder without the addition of anticaking agent. Storage stability of the powder packed in aluminum-laminated polyethylene (ALP) pouches was examined at conventional (25 ± 1°C) and accelerated (38 ± 1°C) temperatures for 91 days until lumpiness was observed. Statistical analysis showed that the addition of anticaking agent significantly (p ≤ 0.05) improved the process yield of powder (7.2%). The moisture content, water activity, density, and water solubility index of the powder were significantly affected by storage time, storage temperature, and concentration of the anticaking agents. The critical moisture content, Xc, for control and powder incorporated with either TCP or CS was 0.07 g H2O/g ds. The total color difference (ΔE) of the powder increased throughout the storage period, followed by a zero-order kinetic reaction. Kinetics-derived Arrhenius model showed that the activation energy (Ea) of color change ranged between 6.5 and 17.3 kJ/mol. Scanning electron microscopy showed that the freshly spray-dried powder was composed of spherical particles with smooth surfaces but these particles tended to agglomerate and form liquid bridges after storage for 91 days. Overall, TCP and CS exhibited a protective effect by lowering moisture adsorption and improved the glass transition temperature of the powder.